2021
DOI: 10.1159/000514100
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Oculomotor Nerve Palsy Displaying Enhancement of the Oculomotor Nerve in the Orbit and Cavernous Sinus on MRI

Abstract: <b><i>Introduction:</i></b> Imaging data were scarce on diabetic oculomotor nerve palsy (ONP). Our study explored the MRI features and their clinical implications for diabetic ONP. <b><i>Methods:</i></b> Fifty-nine patients with a clinical diagnosis of diabetic ONP were recruited from our department between January 2015 and December 2019. Orbital MRI was retrospectively analyzed, and follow-up scans were obtained for 5 patients. Based on the ocular motor nerve pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Currently, only a few studies have reported findings suggestive of OCNPi. One study group showed enhancement of the third cranial nerve on thin-section MRI but did not confirm the same findings of the fourth or sixth cranial nerves, and further validation is needed 18 , 19 . WMH was associated with OCNPi regardless of the cranial nerve involved in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Currently, only a few studies have reported findings suggestive of OCNPi. One study group showed enhancement of the third cranial nerve on thin-section MRI but did not confirm the same findings of the fourth or sixth cranial nerves, and further validation is needed 18 , 19 . WMH was associated with OCNPi regardless of the cranial nerve involved in this study.…”
Section: Discussionmentioning
confidence: 91%
“…39 (2): 149-153 (most common). 7 Conjunctival diseases include tortuous vessels, pingueculae and pterygia. 8 Lesions involving cornea (diabetic keratopathy) include reduced corneal sensitivity characterized by the progressive loss of nerve fibers (leading to reduced blink rate, tear film instability and dry eye), recurrent corneal erosions, superficial punctate keratitis, delayed epithelial healing.…”
Section: Introductionmentioning
confidence: 99%
“…OCN can be affected by many diseases, such as external brain injury (Nakagawa, Toda, Shibao, & Yoshida, 2017), congenital OCN palsy (Yang, Kim, & Hwang, 2020), and brain tumors (Inoue, Hashiguchi, Moroki, & Tokuda, 2020; Li et al, 2018; Taniguchi et al, 2018). Research (Tam, Lonngi, & Demer, 2018; Zhao, Li, Chang, Wang, & Sun, 2021) suggested that identifying the location of OCN is important in guiding diseases that involve the OCN.…”
Section: Introductionmentioning
confidence: 99%
“…Research (Tam, Lonngi, & Demer, 2018;Zhao, Li, Chang, Wang, & Sun, 2021) suggested that identifying the location of OCN is important in guiding diseases that involve the OCN.…”
mentioning
confidence: 99%